The use of bidirectional barbed suture in the treatment of a complete common calcanean tendon rupture in a dog: Long‐term clinical and ultrasonographic evaluation. Issue 8 (10th July 2019) - Frame, Kevin; Ben‐Amotz, Oded; Simpler, Renee; Zuckerman, Josh; Ben‐Amotz, Ron
Abstract: The canine common calcanean tendon can be repaired successfully using a modified Kessler knotless barbed technique. A long‐term ultrasound follow‐up showed improved and increased normal tendon fibrillar echotexture and homogeneity. Abstract : The canine common calcanean tendon can be repaired successfully using a modified Kessler knotless barbed technique. A long‐term ultrasound follow‐up showed improved and increased normal tendon fibrillar echotexture and homogeneity.